DETERMINATION OF HYDRODYNAMIC COEFFICIENTS AND VORTEX INDUCED VIBRATIONS FOR TUBULAR CYLINDERS USING EXPERIMENTAL AND NUMERICAL MODELLING - AL-YACOUBY, AMMAD MAHAMAD (2016)
The present thesis addresses the estimation of hydrodynamic coeflicients for tubular cylinders subjected to oscillatory !lows using wave tank model tests, and presents mathematical models for prediction of hydrodynamic drag and inertia coefficients for Malaysian offshore locations based on linear regression analysis.